2012
DOI: 10.7326/0003-4819-156-10-201205150-00421
|View full text |Cite
|
Sign up to set email alerts
|

Oral Direct Factor Xa Inhibitors Versus Low-Molecular-Weight Heparin to Prevent Venous Thromboembolism in Patients Undergoing Total Hip or Knee Replacement

Abstract: Compared with LMWH, lower doses of oral factor Xa inhibitors can achieve a small absolute risk reduction in symptomatic deep venous thrombosis without increasing bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 46 publications
3
48
2
1
Order By: Relevance
“…Trial‐to‐trial variability in absolute treatment effect was greater than that for relative treatment effect, and the analysis adequately accounted for this heterogeneity and provided a good description of the observed data ( Figures 1 to 4). As described previously,17 although the absolute event rate differs between THR and TKR, no statistically significant difference in the relative treatment effects by type of surgery could be discerned. Similarly, no impact of frequency of administration (once or twice daily) or treatment duration (when studies with the same duration of treatment for all arms were included) was found.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Trial‐to‐trial variability in absolute treatment effect was greater than that for relative treatment effect, and the analysis adequately accounted for this heterogeneity and provided a good description of the observed data ( Figures 1 to 4). As described previously,17 although the absolute event rate differs between THR and TKR, no statistically significant difference in the relative treatment effects by type of surgery could be discerned. Similarly, no impact of frequency of administration (once or twice daily) or treatment duration (when studies with the same duration of treatment for all arms were included) was found.…”
Section: Discussionsupporting
confidence: 51%
“…The availability of different regimens of comparators complicates an integrated assessment of the overall efficacy and safety of new agents relative to the current standard of care, as well as indirect comparisons among the new agents, but this factor has not always been considered in published meta‐analyses for single1, 2, 3, 4, 5, 6, 7 or multiple8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 agents. Dose regimen of the comparator has been acknowledged as a potential source of heterogeneity for a number of previous analyses 1, 2, 3, 5, 6, 10, 11, 12, 13, 14, 18.…”
mentioning
confidence: 99%
“…Both are considered safe for use in pregnancy and can be used in this setting for the treatment and prophylaxis of VTE, in contrast with other available anticoagulant agents that cannot be used in pregnancy either due to known teratogenicity, such as vitamin K antagonists, or lack of established safety information, such as novel oral anticoagulants (NOACs) (Marshall, 2014). In most cases, LMWHs are the preferred agent in VTE treatment and/ or prophylaxis in pregnancy (Hirsh et al, 2001;James, 2007;Regitz-Zagrosek et al, 2011;Bates et al, 2012; and have been shown to be safe and effective in this population (Lepercq et al,…”
Section: B Pregnancymentioning
confidence: 99%
“…The reduced propensity of LMWH to cause the side effects of osteoporosis and thrombocytopenia, compared with UH (Bates et al, 2012;Lussana et al, 2012), may be particularly important in terms of the relatively protracted period of exposure that is indicated in the case of VTE prophylaxis throughout pregnancy and the puerperium. Upward adjustment of normal weight-based regimens tends to be required, especially in the case of LMWHs, in large part because of the increased rate of renal clearance of these agents (secondary to increased volume of distribution) that is associated with pregnancy (Kher et al, 2007).…”
Section: B Pregnancymentioning
confidence: 99%
“…[126][127][128][129] A significant proportion of the arthroplasty associated NOA research to date has been industry supported, and such support may potentially have generated bias in the literature. 127,128,130 Therefore, more studies are required to confirm the relative efficacy of these agents to LMWH.…”
Section: Anticoagulant Safety and Efficacymentioning
confidence: 99%